2018
DOI: 10.1016/j.neuropharm.2017.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating oral flavorant effects on nicotine self-administration behavior and phasic dopamine signaling

Abstract: Understanding how tobacco product flavor additives, such as flavorants in electronic cigarettes, influence smoking behavior and addiction is critical for informing public health policy decisions regarding tobacco product regulation. Here, we developed a combined intraoral (i.o.) and intravenous (i.v.) self-administration paradigm in rats to determine how flavorants influence self-administration behavior. By combining i.o. flavorant delivery with fast scan cyclic voltammetry (FSCV) or i.v. nicotine self-adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…The doses of menthol (up to 5 mg/kg) that were used in the present study were shown to be effective in enhancing nicotine-taking and -seeking behavior in our previous studies (Biswas et al, 2016; Harrison et al, 2017), thus precluding possible concerns about the doses of menthol being too low to produce an effect. The lack of effect of menthol in this microdialysis assay is consistent with a recent report that showed that the intraoral administration of menthol, in contrast to sucrose or saccharin, produced no effect on phasic dopamine release, measured by fast-scan cyclic voltammetry, in the NAc (Wickham et al, 2018). A previous study found that menthol reduced the frequency of dopamine neuron firing in mouse brain slices and cultured neuron preparations (Henderson et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…The doses of menthol (up to 5 mg/kg) that were used in the present study were shown to be effective in enhancing nicotine-taking and -seeking behavior in our previous studies (Biswas et al, 2016; Harrison et al, 2017), thus precluding possible concerns about the doses of menthol being too low to produce an effect. The lack of effect of menthol in this microdialysis assay is consistent with a recent report that showed that the intraoral administration of menthol, in contrast to sucrose or saccharin, produced no effect on phasic dopamine release, measured by fast-scan cyclic voltammetry, in the NAc (Wickham et al, 2018). A previous study found that menthol reduced the frequency of dopamine neuron firing in mouse brain slices and cultured neuron preparations (Henderson et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Rats and humans show affinity for sweet flavors and will readily drink solutions containing either sweetener (Hoffman et al, 2016; Murray et al, 2016). Further, consumption of sucrose or saccharin solution is associated with disruptions in dopamine signaling in the nucleus accumbens (Wickham et al, 2018), an effect that is also observed concomitant with self-administration of abused substances such as cocaine (Saddoris et al, 2016). Indeed, rodents have shown enhanced preference for oral consumption of sucrose solution compared to self-administration of several abused substances, including cocaine, heroin, and nicotine (Cantin et al, 2010; Huynh et al, 2017; Madsen and Ahmed, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Several methods of cigarette smoke exposure have been adopted to establish animal models, such as the whole body, head only, nose only, intraoral nicotine self-administration, and intraoral or transdermal administration of tobacco smoke carcinogens. The whole body exposure to cigarette smoke, perfectly simulating human passive smoking, is the most commonly used approach (Al Hariri et al, 2016; Asci et al, 2018; Schick and Glantz, 2005; Wickham et al, 2018). However, to the best of our knowledge, the intraoral cigarette smoking exposure has not been reported to simulate human active smoking.…”
Section: Introductionmentioning
confidence: 99%